2011
DOI: 10.1124/dmd.111.041947
|View full text |Cite
|
Sign up to set email alerts
|

Studies to Further Investigate the Inhibition of Human Liver Microsomal CYP2C8 by the Acyl-β-Glucuronide of Gemfibrozil

Abstract: ABSTRACT:In previous studies, gemfibrozil acyl-␤-glucuronide, but not gemfibrozil, was found to be a mechanism-based inhibitor of cytochrome P450 2C8. To better understand whether this inhibition is specific for gemfibrozil acyl-␤-glucuronide or whether other glucuronide conjugates are potential substrates for inhibition of this enzyme, we evaluated several pharmaceutical compounds (as their acyl glucuronides) as direct-acting and metabolism-dependent inhibitors of CYP2C8 in human liver microsomes. Of 11 compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
2
25
0
Order By: Relevance
“…The in vivo consequences of the inhibitory effects of these metabolites are discussed in section VI. In an in vitro study by Jenkins et al (2011), the acyl glucuronides of atorvastatin, dehydroketoprofen, diclofenac, ibuprofen, indomethacin, rac-ketoprofen, mefenamic acid, R-and S-naproxen, and simvastatin did not affect CYP2C8 by metabolism-dependent inhibition.…”
Section: B Metabolism-dependent Inhibitionmentioning
confidence: 92%
See 1 more Smart Citation
“…The in vivo consequences of the inhibitory effects of these metabolites are discussed in section VI. In an in vitro study by Jenkins et al (2011), the acyl glucuronides of atorvastatin, dehydroketoprofen, diclofenac, ibuprofen, indomethacin, rac-ketoprofen, mefenamic acid, R-and S-naproxen, and simvastatin did not affect CYP2C8 by metabolism-dependent inhibition.…”
Section: B Metabolism-dependent Inhibitionmentioning
confidence: 92%
“…The benzylic oxidation of the glucuronide by CYP2C8 leads to haem alkylation and irreversible inactivation of CYP2C8 (Baer et al, 2009;Jenkins et al, 2011). In HLM, the k inact value of CYP2C8 by gemfibrozil 1-O-b-glucuronide has been 0.21 1/min and K I 20-52 mM (Ogilvie et al, 2006).…”
Section: A General Aspectsmentioning
confidence: 99%
“…Gemfibrozil glucuronide is often quoted as an example of a metabolite that causes significant DDI through inhibition of CYP2C8. This is certainly an exceptional case, and the presence of a mechanism-based inhibitor that is formed through further metabolism of a glucuronide is quite unique (Ogilvie et al, 2006;Jenkins et al, 2011). However, gemfibrozil is itself an inhibitor of CYP2C8 in vitro.…”
Section: Consideration Of Clinically Relevant Levels and Inhibition Pmentioning
confidence: 99%
“…Contrasting with the in vitro findings, gemfibrozil-mediated pharmacokinetic interactions in vivo are mostly reported with CYP2C8 substrate drugs as exemplified by cerivastatin (5.6-fold increase in parent drug AUC) (Backman et al, 2002), montelukast (4.5-fold) (Karonen et al, 2010), atorvastatin (1.4-fold) (Whitfield et al, 2011), pioglitazone (3.4-fold) (Deng et al, 2005), loperamide (2.9-fold) (Niemi et al, 2006), rosiglitazone (2.3-fold) (Niemi et al, 2003), and repaniglide (7.0-fold) (Tornio et al, 2008). In large part, these interactions observed in vivo are not caused by gemfibrozil itself but by its 1-O-␤-glucuronide metabolite, which is a specific CYP2C8 mechanism-based inhibitor with a K i of 20 to 52 M and a k inact of 0.21 min Ϫ1 (Ogilvie et al, 2006;Jenkins et al, 2011). The glucuronide provides plasma peak concentrations close to those of the parent drug (Tornio et al, 2008), shows lower plasma protein binding (88.5 and 99.4%, respectively) (Shitara et al, 2004), and is reported to accumulate in the liver (Sabordo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%